Accurate determination of rivaroxaban levels requires different calibrator sets but not addition of antithrombin - Mani, Helen; Rohde, Gabriele; Stratmann, Gertrud; Hesse, Christian; Herth, Natalie; Schwers, Stephan; Perzborn, Elisabeth; Lindhoff-Last, Edelgard (Thrombosis and Haemostasis, 2012)
Rivaroxaban is a direct factor Xa inhibitor, which can be monitored by anti-factor Xa chromogenic assays. This ex vivo study evaluated different assays for accurate determination of rivaroxaban levels. Eighty plasma samples from patients receiving rivaroxaban (Xarelto®) 10 mg once daily and 20 plasma samples from healthy volunteers were investigated using one anti-factor Xa assay with the addition of exogenous antithrombin and two assays without the addition of antithrombin. Two different lyophilised rivaroxaban calibration sets were used for each assay (low concentration set: 0, 14.5, 59.6 and 97.1 ng/ml; high concentration set: 0, 48.3, 101.3, 194.2 and 433.3 ng/ml). Using a blinded study design, the rivaroxaban concentrations determined by the assays were compared with concentrations measured by HPLC-MS/MS. All assays showed a linear relationship between the rivaroxaban concentrations measured by HPLC-MS/MS and the optical density of the anti-FXa assays. However, the assay with the addition of exogenous anti-thrombin detected falsely high concentrations of rivaroxaban even in plasma samples from controls who had not taken rivaroxaban (intercept values using the high calibrator set and the low calibrator set: +26.49 ng/ml and +13.71 ng/ml, respectively). Plasma samples, initially determined by the high calibrator setting and containing rivaroxaban concentrations <25 ng/ml, had to be re-run using the low calibrator setting for precise measurement. In conclusion, anti-factor Xa chromogenic assays that use rivaroxaban calibrators at different concentration levels can be used to measure accurately a wide range of rivaroxaban concentrations ex vivo. Assays including exogenous antithrombin are unsuitable for measurement of rivaroxaban.
Keywords: Coagulation inhibitors; haemostasis; coagulation factors; rivaroxaban; anti-Xa